Nutrition Transition in Europe: East-West Dimensions in the Last 30 Years—A Narrative Review - Dokova, Klara G.; Pancheva, Rouzha Z.; Usheva, Natalya V.; Haralanova, Galina A.; Nikolova, Silviya P.; Kostadinova, Todorka I.; Egea Rodrigues, Caue; Singh, Jessica; Illner, Anne-Kathrin; Aleksandrova, Krasimira (Frontiers in Nutrition, 2022)
The current review aims to summarise published research on nutrition transition patterns (depicting changes in dietary consumption) in European populations over the last three decades (1990-2020), with a focus on East-West regional comparisons. Pubmed and Google-Scholar databases were searched for articles providing information on repeated dietary intakes in populations living in countries across Europe, published between January 1990 and July 2021. From the identified 18,031 articles, 62 were found eligible for review (17 from Eastern and 45 from Western European populations). Overall, both in Eastern and Western Europe, there have been pronounced changes in dietary consumption patterns over the last three decades characterized by reductions in average reported intakes of sugar, carbohydrates and saturated fats and increases in reported fruit and vegetable consumption. There has also been a tendency towards a reduction in traditional foods, such as fish, observed in some Mediterranean countries. Overall, these data suggests that European countries have undergone a nutrition transition towards adopting healthier dietary behaviours. These processes occurred already in the period 1990-2000 in many Western European, and in the last decades have been also spreading throughout Eastern European countries. Firm conclusions are hampered by the lack of standardized methodologies depicting changes in dietary intakes over time and the limited coverage of the full variety of European populations. Future studies based on standardised dietary assessment methods and representative for the whole range of populations across Europe are warranted to allow monitoring trends in nutrition transition within and among European countries.